Hermeneutic conjugation of learning throug practics for the university teacher formative - Argota Pérez, George (2019)
The purpose of study was to combine the hermeneutics of learning through practices for university teacher training. The study was carried out at the National University ̈San Luis Gonzaga ̈ of Ica during 2018 where it was considered in the international diploma program “Scientific Creativity and Technological Innovation”, the training learning of university teachers. Three university teachers were selected by means of a random probability sampling, giving them the same scientific article for the analysis and methodological recognition of six indicators: 1st) selection variable, 2nd) research approach, 3rd) type of scientific article oriented, 4th) recognition cognitive, 5th) methodological structure of interest and 6th) criterion of interpretation and contribution. The results were compared to a response key. Then, the level of learning was assessed by means of a psycho-labor test of speed and a test by scale of understanding. 10 points were assigned as the maximum value to each test considering the result to be excellent, if the score is in the range of 18 to 20 points. The average scores according to the response to the six indicators was 10.66 points while, for the tests it was 15.16 points. The low score shows difficulty in interpreting methodological structures and concepts. It is concluded that, university teaching training to be considered acceptable must be incorporated permanently, the practical interpretation of procedural and conceptual conjugations where the analysis and situational assessment of critical judgment in the understanding of learning is oriented.